(untitled) (Al-Qamar, 2024)
Maulana Hafiz Ghulam Murtaza (1251 AH / 1835 AD to 1321 AH / 1903 AD) was a leading scholar of the 19th century. He spent his whole life acquiring and then spreading knowledge among his people. The end of the thirteenth century AH and the beginning of the fourteenth century AH was his era span. It was very difficult time for the Muslims of the subcontinent. This turbulent period saw many revolutions. There was a lack of political and religious leadership for Muslims as a whole. There were no standard educational institutions for Muslims, and Muslims in general had excluded education from their priorities. They were satisfied with their ignorance. Especially after the War of Independence of 1857, Muslims suffered a complete decline. Hafiz Ghulam Murtaza lit the candle of knowledge in a remote area of ​​Punjab in subcontinent where human beings were suffering from the double bondage of feudalism and ignorance, the rays of which, after a century and a half, are still illuminating an era. The article under review gives a brief overview of the scholarly and religious services of this religious and visionary scholar. The purpose of this article is to make the world aware of the fact that there are such bright lights of knowledge and spirituality under the banner of Islam, that even a thousand glooms of ignorance together cannot face a ray of their knowledge.